Aluminum component and method for manufacturing the same

Friction stir processing with a low-speed cylindrical clamp creates fine grain regions in high-purity aluminum, addressing strength and conductivity issues, resulting in a strong and conductive aluminum component.

CN116134168BActive Publication Date: 2024-12-27SUMITOMO CHEM CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202180059555.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-30
Filing Date
2021-07-29
Publication Date
2024-12-27
Estimated Expiration
2041-07-29

AI Technical Summary

Technical Problem

Existing methods fail to sufficiently refine the crystal grain size of aluminum with a purity of 5N or higher, resulting in insufficient strength for applications requiring strength.

Method used

A method involving friction stir processing with a rotating cylindrical clamp at a low moving speed and specific inclination is used to create a fine grain region with a crystal grain size of less than 20 μm, combined with intermediate and coarse grain regions, to enhance strength and conductivity in aluminum components.

Benefits of technology

The method achieves an aluminum component with a purity of 5N or more, exhibiting sufficient strength and excellent electrical and thermal conductivity at extremely low temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116134168B_ABST
    Figure CN116134168B_ABST
Patent Text Reader

Abstract

An aluminum component includes a fine crystal grain region with a crystal grain size of less than 20 μm, wherein the purity of the aluminum component is 99.999 mass % or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an aluminum component and a method for manufacturing the same. Background Art

[0002] Aluminum (Al) with a purity of 99.999 mass % (5N) or more has extremely high electrical and thermal conductivity at extremely low temperatures, and is therefore often used as an electrical and thermal conductor for extremely low-temperature equipment.

[0003] However, Al has a tendency to have lower strength as its purity increases, limiting its uses. In applications where strength is required, methods such as bonding high-strength materials to Al above 5N or adding heterogeneous elements (alloying) can be used, but these methods have the problems of high costs and loss of the excellent properties of Al above 5N.

[0004] As a method for improving the strength of metal materials such as Al, a method of refining the crystal grain size can be cited. In non-patent document 1, it is disclosed that the crystal grain size of Al with a purity of 99.99 mass% (4N) can be refined to about 2μm by high-pressure huge strain processing, so that it can be highly strengthened to a hardness of 40HV. In non-patent document 2, it is disclosed that for 4N Al, by performing friction stir processing (Friction Stir Processing: FSP) under the conditions of a moving speed of 200mm / min and a rotation number of 300 to 1500rpm, the crystal grain size can be reduced to a minimum of less than 2μm.

[0005] Prior art literature

[0006] Non-patent literature

[0007] Non-patent document 1: Yoshiharu Horita, "Ultrafine structure control using giant strain processing (Japanese: Ultrafine structure control using giant strain processing)", Light Metals, Japan Society of Light Metals, 2010, Vol. 60, No. 3, p134-141

[0008] Non-patent document 2: Shigeki Mori, “Optimization of microstructure of ultrafine grain aluminum material using friction stir processing”, PhD thesis, Graduate School of Osaka Prefecture University, 2011 Summary of the invention

[0009] Problems to be solved by the invention

[0010] However, in the prior art disclosed in non-patent documents 1 and 2, it is impossible to sufficiently refine the crystal grain size of Al above 5N. Non-patent document 1 discloses the following points: if the purity of Al is high, cross-slip and / or recovery of dislocations are easy to occur, and sufficient accumulation of dislocations does not occur, and the crystal grain size is not refined. Non-patent document 2 discloses that even if the conditions that can make 4N Al a minimum of 2μm or less are applied to 5N Al, the crystal grain size is still about 30μm, and discloses the following points: for the large difference in the crystal grain size, only a very small amount of impurity elements of about 100ppm will have a great impact.

[0011] From the above, it cannot be said that the prior art discloses a method for sufficiently miniaturizing the crystal grain size of Al above 5N. Therefore, in the prior art, Al above 5N has insufficient overall strength and is difficult to use in applications requiring strength.

[0012] The present invention has been made in view of the above circumstances, and one of its objects is to provide an aluminum member having a purity of 5N or higher and having sufficient strength in at least a portion thereof, and a method for producing the same.

[0013] Means for solving problems

[0014] A first aspect of the present invention is an aluminum member including a fine grain region having a crystal grain size of less than 20 μm.

[0015] Furthermore, the purity of the aluminum component is 99.999% by mass or more.

[0016] The second aspect of the present invention is the aluminum member according to the first aspect, further comprising:

[0017] An intermediate crystal grain region having a crystal grain size of 20 μm or more and less than 150 μm, and a coarse crystal grain region having a crystal grain size of 150 μm or more.

[0018] A third aspect of the present invention is the aluminum member according to the first or second aspect, wherein an average grain size of the fine grain region is 5 μm or less.

[0019] A fourth aspect of the present invention is the aluminum member according to any one of the first to third aspects, wherein the fine crystal grain region exists continuously with a thickness of 0.01 mm on at least one surface. 2 The area above.

[0020] A fifth aspect of the present invention is an extremely low temperature electrically conductive and thermally conductive material comprising the aluminum member according to any one of the first to fourth aspects.

[0021] Aspect 6 of the present invention is a method for manufacturing an aluminum component as described in any one of aspects 1 to 4, which includes a friction stirring process of pressing and moving a rotating cylindrical clamp on the surface of an aluminum plate with a purity of 99.999% or more by mass, wherein the moving speed of the cylindrical clamp is less than 100 mm / minute.

[0022] The seventh aspect of the present invention is a method according to the sixth aspect, wherein, in the friction stirring process, the rotation axis of the cylindrical clamp is moved from a vertical line of the surface of the aluminum plate to a direction opposite to the moving direction of the cylindrical clamp at an inclination of more than 3°.

[0023] Effects of the Invention

[0024] According to the embodiment of the present invention, it is possible to provide an aluminum member having a purity of 5N or more and having sufficient strength in at least a portion thereof, and a method for manufacturing the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is an image of the inverse pole figure (IPF) of Example 1 using the EBSD method.

[0026] Figure 2 for Figure 1 Enlarged view of the fine grain area 1. DETAILED DESCRIPTION

[0027] The present inventors have conducted studies from various viewpoints in order to realize an aluminum member having a purity of 5N or higher and having sufficient strength in at least a portion thereof.

[0028] As a method for realizing the above-mentioned aluminum component, the present inventors and others have focused on friction stir processing (FSP). In FSP, a rotating cylindrical fixture is pressed against a processed material and moved, thereby applying a strong strain to the processed material. In research on FSP, it is believed that the strong strain can cause dynamic recrystallization in the processed material to form fine recrystallized grains. According to the prior art, especially non-patent document 2, it is speculated that in FSP, by moving the cylindrical fixture at a relatively fast speed (specifically 200 mm / min), processing heat can be reduced and grain growth can be suppressed.

[0029] As a result of in-depth research by the inventors, it was found that, unlike previous technical ideas, by moving the cylindrical fixture at a relatively low speed (below 100 mm / minute), it is possible to achieve a fine-grained region with a crystal grain size of less than 20 μm, which is impossible to achieve with the prior art, for Al with a purity of 5N or above, and further, the portion containing the fine-grained region has sufficient strength (Vickers hardness).

[0030] The following is a detailed description of each requirement specified in the embodiment of the present invention. It should be noted that the "purity" of the aluminum component (and aluminum plate) in the embodiment of the present invention refers to the value obtained by removing the total content (mass %) of the three main impurity components (Si, Fe and Cu) from 100 mass %.

[0031] The purity of the aluminum member according to the embodiment of the present invention is 99.999% by mass or more. This can improve the low temperature conductivity of the aluminum member. Preferably, the purity is 99.9995% by mass or more.

[0032] The aluminum component of the embodiment of the present invention may contain other trace impurity 10 elements (Ti, Mn, Mg, B, Cr, Ga, Ni, V, Zn, Zr) in addition to the main impurity 3 components (Si, Fe and Cu). The content of the other trace impurity 10 elements is preferably 0.001 mass% or less. Thereby, the extremely low temperature conductivity of the aluminum component can be improved.

[0033] The aluminum member according to the embodiment of the present invention includes a fine crystal grain region having a crystal grain size of less than 20 μm. Thus, an aluminum member having sufficient strength in at least a portion (ie, a portion including the fine crystal grain region) can be obtained.

[0034] The average grain size of the fine grain region measured at 100 μm is less than 20 μm, preferably less than 5 μm, and more preferably less than 3 μm. This can further improve the strength of the fine grain region. The lower limit of the average grain size in the fine grain region is not particularly limited, and can be, for example, 0.1 μm or more.

[0035] The fine grain region preferably has a diameter of 0.01 mm. 2 The above continuous part. Thus, the strength can be improved.

[0036] The fine crystal grain region preferably has a portion exposed on at least one surface of the aluminum member. This can improve the strength against external forces from the outside.

[0037] In addition, it is preferred that the fine crystal grain region has a continuous thickness of 0.01 mm on at least one surface of the aluminum member. 2 More preferably 1mm 2 More than 10 mm is more preferred 2 More preferably, there is a continuous 40 mm 2 Thereby, the strength against external forces from the outside can be improved. There is no particular upper limit for the above area, which can be 1.5m 2Below. In addition, on at least one surface of the aluminum component, the above-mentioned fine grain region preferably exists continuously for an area of ​​more than 0.001 area%, more preferably more than 0.1 area%, further preferably more than 1 area%, and further preferably more than 4 area%. For the above-mentioned area ratio, the upper limit is not particularly limited, and it can be less than 100 area%. It should be noted that as a method for measuring the continuous area of ​​the fine grain region on the surface of the aluminum component, it can be measured by, for example, performing EBSD analysis on the surface described later. Alternatively, EBSD analysis can be performed on a cross-section parallel to the long side direction (or short side direction) of the aluminum component on the surface and perpendicular to the surface, and the analysis can be repeated at regular intervals (for example, 0.02 mm) in the short side direction (or long side direction), thereby measuring the continuous area of ​​the fine grain region on the surface of the aluminum component.

[0038] The above-mentioned fine grain region preferably has a portion with a thickness of 0.10 mm or more measured from at least one surface of the aluminum component toward the back surface. It is more preferred to have a portion with a thickness of 0.20 mm or more, and it is further preferred to have a portion with a thickness of 0.30 mm or more. In this way, the strength against external forces from the outside can be improved. In addition, it is preferred to have a portion with a ratio of 10% or more of the thickness of the fine grain region relative to the length from the surface to the back surface of the aluminum component, more preferably a portion with a ratio of 20%, and further preferably a portion with a ratio of 30%. In this way, the strength against external forces from the outside can be improved.

[0039] The area of ​​the fine grain region may decrease from at least one surface of the aluminum member according to the embodiment of the present invention toward the back surface. In addition, the area of ​​the fine grain region may be different between at least one surface and the back surface.

[0040] The aluminum member according to the embodiment of the present invention may include a non-fine grain region with a grain size of 20 μm or more in addition to the fine grain region. For example, it may further include an intermediate grain region with a grain size of 20 μm or more and less than 150 μm, and a coarse grain region with a grain size of 150 μm or more.

[0041] From the perspective of improving strength, it is preferred to increase the fine grain region, and it is preferred to reduce the intermediate grain region and the coarse grain region, wherein reducing the coarse grain region is more preferred. From the perspective of improving strength, a preferred embodiment is that the aluminum component is composed of a fine grain region and an intermediate grain region, and from the perspective of improving strength, the most preferred embodiment is that the aluminum component is composed of a fine grain region.

[0042] On the other hand, by including a coarse grain region (and / or an intermediate grain region), the number of grain boundaries is reduced, and the extremely low temperature conductivity can be improved. As a preferred embodiment based on the viewpoint of having both strength and extremely low temperature conductivity in a balanced manner, the aluminum component includes a fine grain region in a portion where strength is required, and includes a coarse grain region (and / or an intermediate grain region) in the portion other than the fine grain region.

[0043] In the embodiment of the present invention, the crystal grain size refers to the diameter of the area of ​​the region surrounded by the grain boundary with a crystal orientation difference of 5° or more as the grain boundary in the result of the electron beam backscatter diffraction (EBSD) analysis, i.e., the equivalent circle diameter, and the average crystal grain size refers to the average value of the crystal grain size in the specified area (e.g., 100 μm□) of the surface analyzed by EBSD. It should be noted that, for the coarse grain region, as a simple method for calculating the average crystal grain size, a straight line can be drawn on the surface analyzed by EBSD, and the value obtained by dividing the length of the straight line by the number of grain boundaries intersecting the straight line is used as the average crystal grain size of the coarse grain region.

[0044] The aluminum member according to the embodiment of the present invention may be in any shape, for example, a plate shape, a thin wire shape, or a cylindrical shape.

[0045] The extremely low temperature electrically conductive and thermally conductive material according to the embodiment of the present invention includes the above-mentioned aluminum member, and may include other members in addition to the above-mentioned aluminum member within the scope of achieving the object of the present invention.

[0046] The manufacturing method of the aluminum component according to the embodiment of the present invention includes a friction stirring process of pressing a rotating cylindrical fixture on the surface of an aluminum plate having a purity of 99.999% or more by mass while moving the cylindrical fixture, wherein the moving speed of the cylindrical fixture is 100 mm / min or less. Thus, a fine grain region having a crystal grain size of less than 20 μm and a grain size of 5N or more can be formed at a portion to which a strong strain is applied by the cylindrical fixture.

[0047] In the above-mentioned friction stirring process, the aluminum plate to be processed can be set as one sheet. In addition, the friction stirring process can be performed multiple times on the same part of the surface of one aluminum plate, or once or multiple times on different parts. It should be noted that the friction stirring process can also be performed on the entire surface (and / or back side) of one aluminum plate to form a fine grain region in the entire area of ​​the aluminum plate.

[0048] In the above-mentioned friction stirring process, the aluminum plate to be processed can also be set to multiple pieces, for example, two pieces. In this case, the two aluminum plates are placed on the same plane, and one end surface of the two aluminum plates is brought into contact with each other, and a rotating cylindrical fixture is pressed against the contact portion on the surface of the two aluminum plates while moving it. In this way, an aluminum component can be obtained in which two aluminum plates are joined, and a fine grain area with a crystal grain size of less than 20μm is formed in a portion near the joint where a strong strain is applied. It should be noted that the friction stirring process can be performed on the joint multiple times, and the friction stirring process can also be performed outside the joint. It is preferred that the thickness of the multiple aluminum plates is the same because the cylindrical fixture can be pressed evenly. In addition, for the multiple aluminum plates, it is preferred to have at least one flat end surface so that they can contact each other without a gap.

[0049] In the friction stirring step, the moving speed of the cylindrical fixture is preferably 80 mm / min or less, more preferably 20 mm / min or less, and further preferably 8 mm / min or less. This can further reduce the average grain size of the fine grain region.

[0050] In the friction stirring step, the cylindrical fixture is preferably moved so that the rotation axis of the cylindrical fixture is tilted by more than 3° from the vertical line of the aluminum plate surface to the direction opposite to the moving direction of the cylindrical fixture. As a result, the rotation force generated by the cylindrical fixture is easily directed from the surface of the aluminum plate to the inside, which makes it easy to expand the fine grain area. The upper limit of the angle of the tilted cylindrical fixture is, for example, 85°.

[0051] In the friction stirring process, the rotation speed of the cylindrical fixture is preferably set to more than 1500 rpm, more preferably more than 2000 rpm, and further preferably more than 3000 rpm. Thus, the grains are easily miniaturized. The upper limit of the rotation speed of the cylindrical fixture is not particularly limited, for example, it is less than 20000 rpm.

[0052] In the above-mentioned friction stirring process, the depth of the cylindrical fixture pressed into the surface of the aluminum plate is preferably set to be greater than 0.3 mm and less than 3 mm, and more preferably greater than 0.3 mm and less than 0.5 mm. In addition, the ratio of the pressing depth to the thickness of the aluminum plate is preferably greater than 6% and less than 100%, and more preferably greater than 37.5% and less than 62.5%. As a result, the friction stirring process can be carried out at an appropriate processing speed, and a fine grain area can be easily obtained. After the friction stirring process, a recess can be formed on the surface of the aluminum component according to the pressing depth of the cylindrical fixture.

[0053] In the friction stirring step, the cylindrical fixture may be made of a material having a higher hardness than aluminum, such as tool steel, etc. The front end of the cylindrical fixture may be spherical or other shapes.

[0054] In the friction stirring step, the aluminum plate with a purity of 99.999% by mass or more, which is the processed material, can be prepared by a known method. For example, an aluminum sheet with a purity of 99.999% by mass or more can be prepared by a known method such as a segregation method, a three-layer electrolysis method, a belt melting refining method, an ultra-high vacuum melting refining method, or a combination thereof, and then rolled to prepare the aluminum sheet.

[0055] In the above-mentioned friction stirring process, the thickness of the aluminum plate that becomes the processed material is preferably 0.5 mm or more, and more preferably 0.7 mm or more. Thus, the deformation of the aluminum plate in the friction stirring process can be suppressed. The upper limit of the thickness of the aluminum plate is not particularly limited, for example, it is 5 mm or less. In addition, the in-plane shape of the aluminum plate is not particularly limited, for example, it can be set to a square or a rectangle.

[0056] In the aluminum member obtained after the friction stirring step, the area of ​​the fine grain region may decrease from the surface of the cylindrical jig toward the back surface. This is considered to be because the range of strong strain applied by the cylindrical jig decreases from the surface of the cylindrical jig toward the back surface.

[0057] In the aluminum component obtained after the above-mentioned friction stirring process, since strong strain can be continuously applied from the surface of the pressing cylindrical fixture to the back side, the fine grain region can be made continuous from the surface to the back side, and depending on the situation, the fine grain region can be made continuous from the surface to the back side. In most cases, the area of ​​the fine grain region is different between the surface and the back side of the pressing cylindrical fixture, and the area of ​​the fine grain region can be larger on the surface of the pressing cylindrical fixture than on the back side. It is believed that this is because the surface of the pressing cylindrical fixture is subjected to strong strain in a wider range.

[0058] In the region where almost no strain is applied in the friction stirring step, grain refinement does not occur, and the region may become a coarse grain region with a grain size of 150 μm or more, for example.

[0059] In the aluminum component obtained after the friction stirring process, the surface on which the cylindrical jig is pressed can reduce the area of ​​the coarse grain region compared to the back surface. That is, in the aluminum component obtained after the friction stirring process, the area of ​​the coarse grain region can be different on at least one surface and the back surface. It is believed that this is because the surface on which the cylindrical jig is pressed is subjected to strong strain in a larger range, and conversely, the area to which almost no strain is applied becomes smaller.

[0060] Through the friction stirring process, an intermediate grain region with a crystal grain size of 20 μm or more and less than 150 μm can also be formed. The intermediate grain region can be formed, for example, between the fine grain region and the coarse grain region. It is believed that this is because the influence of the cylindrical fixture is smaller between the fine grain region and the coarse grain region than in the fine grain region, and the influence of the cylindrical fixture is greater than in the coarse grain region.

[0061] Within the scope of achieving the purpose of the present invention, the manufacturing method of the aluminum component of the embodiment of the present invention may also include other steps, for example, it may also include a step of processing into various shapes such as fine wires, a step of flattening the surface of the aluminum component and / or a step of removing coarse grain areas.

[0062] Example

[0063] The embodiments of the present invention are not limited to the following embodiments, but can be implemented by appropriately adding changes within the scope of the above and the following principles, and these are all included in the technical scope of the embodiments of the present invention.

[0064] Aluminum sheets (thickness 20 mm) with a purity of 5N prepared by a known method are cold rolled at room temperature to obtain aluminum plates with a width of 10 mm, a length of 100 mm, and a thickness of 0.8 mm. The rolling direction is the length direction. Two sheets of the aluminum sheets are prepared and placed on the same plane, so that the end faces (width 10 mm × thickness 0.8 mm) of the two sheets in the length direction are in contact with each other, and a rotating cylindrical fixture is pressed against the contacting portion of the surfaces of the two sheets while the cylindrical fixture is moved a distance of 10 mm at a speed of 5 mm / min. At this time, the cylindrical fixture used is made of tool steel SKD61, and the front end shape is set to a spherical surface with a diameter of 5 mm and a curvature of 5.4 mm. The rotation speed of the cylindrical fixture is set to 3000 rpm, and the rotation axis of the cylindrical fixture is moved by tilting more than 3° from the vertical line of the aluminum sheet surface to the direction opposite to the moving direction of the cylindrical fixture. The depth of the cylindrical jig pressed into the surface of the aluminum plate was set to 0.35 mm.

[0065] According to the above, the aluminum member of Example 1 was obtained. Furthermore, the moving speed of the cylindrical jig and the depth of the press into the aluminum plate surface were changed as shown in Table 1, and the aluminum members of Examples 2 and 3 were obtained.

[0066] [Table 1]

[0067]

[0068] Aluminum sheets (thickness 20 mm) with a purity of 4N, 5N or 6N prepared by a known method were cold rolled at room temperature to obtain aluminum components (aluminum plates) of Comparative Examples 1 to 5 (only the plate thickness of Comparative Example 4 was 1.0 mm, and the plate thickness of the other plates was 0.8 mm). Subsequently, heat treatment was performed at 500°C for 3 hours in a nitrogen atmosphere for Comparative Examples 4 to 5.

[0069] Examples 1 to 3 and Comparative Examples 1 to 5 were evaluated as follows.

[0070] <Impurity concentration measurement>

[0071] Examples of the impurity concentration measurement method include glow discharge mass spectrometry (GD-MS) or solid emission spectrometry. Examples 1 to 3 and Comparative Examples 4 and 5 measured the impurity concentration by GD-MS, and Comparative Examples 1 to 3 measured the impurity concentration by solid emission spectrometry.

[0072] The results of measuring the contents (mass %) of the main elements Fe, Si and Cu and their total value, as well as the total content of other trace impurity 10 elements (Ti, Mn, Mg, B, Cr, Ga, Ni, V, Zn, Zr) are shown in Table 2.

[0073] [Table 2]

[0074]

[0075] <Average crystal particle size measurement>

[0076] In Examples 1 to 3, the cross-section parallel to the length direction (rolling direction) and the thickness direction was mirror-finished by polishing with colloidal silica. Afterwards, the cross-section was subjected to crystal orientation analysis using the electron beam backscatter diffraction (EBSD) method. The step size during EBSD measurement was set to 0.2 μm, and the boundary where the orientation difference between adjacent pixels was 5° or more was set as the grain boundary.

[0077] As an example, Figure 1 The IPF image of the cross section parallel to the length direction (rolling direction) and the thickness direction of Example 1 using the EBSD method is shown. It should be noted that in the basic application (Japanese Patent Application, Japanese Patent Application No. 2020-129167), Figure 1 (and the following Figure 2 ), in order to understand the difference in crystal planes in more detail, an original image that can identify the difference in crystal planes by color is provided as an object proposal. Please refer to this original image as needed.

[0078] exist Figure 1In the 3D image, the fine grain region 1 was observed in the area (about 4 mm in the length direction) where the cylindrical fixture was pressed on the surface of the aluminum component. It should be noted that the grains in the fine grain region 1 are very fine and there are many grain boundaries (black lines). Figure 1 In the IPF image, it looks almost black. In addition, coarse grain region 3 was observed in the area where the cylindrical fixture was not pressed on the surface of the aluminum component and in the area away from the fine grain region 1, and intermediate grain region 2 was observed between the fine grain region 1 and the coarse grain region 3. It should be noted that in Example 1, the fine grain region was formed in the entire area (about 4 mm×10 mm) where the cylindrical fixture was pressed on the surface of the aluminum component.

[0079] The same structure is also used in Examples 2 and 3.

[0080] Figure 2 express Figure 1 Enlarged view of fine grain region 1 (100 μm × 100 μm). Figure 2 The average grain size of the fine grain region of Example 1 is taken as the average grain size of the fine grain region of Example 1. For the intermediate grain region, extract Figure 1 The total of the intermediate grain region 2 contained in the extracted intermediate grain region is calculated. For the coarse grain region, in the cross section parallel to the length direction (rolling direction) and the thickness direction, a straight line of about 15 mm in length is drawn in the length direction, and the number of grain boundaries intersecting the straight line is counted. The straight line length is divided by the number of grain boundaries as the grain size. The grain boundaries are counted at any 2 or more locations in the cross section, and the average value of the obtained grain size is set as the average grain size of the coarse grain region.

[0081] For Examples 2 and 3, also Figure 1 The average crystal grain size was measured in the same manner.

[0082] In Comparative Examples 1 to 5, the cross-section parallel to the rolling direction and the plate thickness direction was mirror-finished, and the microstructure was revealed by etching. Thereafter, a straight line of about 15 mm in length was drawn in the rolling direction, and the number of grain boundaries intersecting the straight line was counted. The length of the straight line was divided by the number of grain boundaries as the crystal grain size. The counting of the grain boundaries was performed at any two or more locations on the observation surface, and the average value of the obtained crystal grain sizes was set as the average crystal grain size.

[0083] <Hardness measurement>

[0084] As an indicator of whether or not at least a portion of the obtained aluminum member has sufficient strength, the Vickers hardness (HV) was measured using a micro-Vickers hardness tester.

[0085] Vickers hardness is a value measured in accordance with JIS Z2244:2009 "Vickers hardness test - test method". In the measurement of Vickers hardness, a diamond indenter in the shape of a regular quadrangular pyramid is pressed into the surface of a test piece of an aluminum member, and after the test force is released, the diagonal length of the depression remaining on the surface is calculated.

[0086] The test load can be adjusted arbitrarily. For example, the test piece thickness and the test load can be selected in such a way that the test piece thickness is 1.5 times or more of the diagonal length of the indentation as described in JIS Z2244:2009. As a preferred example of the test load, 0.05 kgf can be cited when the thickness of the aluminum component is 300 μm or more, and 0.005 to 0.01 kgf can be cited when the thickness is less than 300 μm. In addition, the test load can be adjusted according to the hardness of the test piece so that the indentation size is appropriate.

[0087] In Examples 1 to 3, the hardness of the area (about 4 mm×10 mm) on the surface of the aluminum member where the cylindrical fixture was pressed was measured at any four or more locations, and in Comparative Examples 1 to 3, the hardness was measured at any four or more locations where the measurement location was not specifically designated, and the average value of each measurement location was calculated. In Comparative Examples 4 and 5, the hardness was not measured.

[0088] When the hardness is 35 (HV) or more, it is judged that the steel has sufficient strength.

[0089] The results of the measurement of the average crystal grain size and hardness of Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 3. It should be noted that in Examples 1 to 3, the column "Average crystal grain size" records the average crystal grain size of the fine grain region. In addition, although not recorded in Table 3, the average crystal grain size of the coarse grain region of Examples 1 to 3 is 890 μm, and the average crystal grain size of the intermediate grain region of Example 1 is 110 μm. In addition, in Comparative Examples 1 to 5, there is no fine grain region with a crystal grain size of less than 20 μm.

[0090] [Table 3]

[0091]

[0092] The results in Table 3 can be considered as follows. Examples 1 to 3 in Table 3 are all examples that meet all the requirements specified in the embodiments of the present invention, and have sufficient strength despite the purity of 5N or more. In particular, in Examples 1 to 2, unlike Example 3, the moving speed of the cylindrical fixture meets the preferred range of 80 mm / min or less, thereby showing a more excellent result that the average crystal grain size in the fine grain area is 5 μm or less and the hardness is 40 (HV) or more. In addition, in Example 1, unlike Examples 2 and 3, the moving speed of the cylindrical fixture meets the more preferred range of 20 mm / min or less, thereby showing a further excellent result that the average crystal grain size in the fine grain area is 3 μm or less and the hardness is 60 (HV) or more.

[0093] On the other hand, when the purity was lowered to 4N as in Comparative Example 1, sufficient strength was exhibited. However, Comparative Examples 2 and 3 with a purity of 5N or more did not contain a fine crystal grain region with a crystal grain size of less than 20 μm, and thus had insufficient strength.

[0094] <Evaluation of ultra-low temperature conductivity characteristics (evaluation of residual resistance ratio)>

[0095] The resistance is measured by the four-terminal method. The resistance is measured in the state where the sample is immersed in liquid helium and in the state where it is immersed in water controlled to 23°C, and the ratio of the resistance in the liquid helium immersed state to the resistance measured at 23°C (residual resistance ratio: RRR) is obtained. The case where the residual resistance ratio is greater than 1000 is judged to be excellent in ultra-low temperature conduction characteristics. It should be noted that in Example 1, the resistance is measured in a manner such that the area (about 4mm×10mm) on the surface of the aluminum component where the cylindrical clamp is pressed is included between the terminals.

[0096] The measurement results of the residual resistance ratio are shown in Table 4. In Example 1, the column "average crystal grain size" describes the average crystal grain size of the fine crystal grain region.

[0097] [Table 4]

[0098]

[0099] The following conclusions can be drawn from the results in Table 4: Example 1 satisfies all the requirements specified in the embodiment of the present invention, and has a purity of 5N or more, and thus has excellent ultra-low temperature conduction characteristics.

[0100] On the other hand, in Comparative Example 4, the purity was 4N, and thus the extremely low temperature conduction characteristics were insufficient.

[0101] It should be noted that the purity of Example 1 and Comparative Example 5 is 5N or more, but the number of grain boundaries in Example 1 is large, and the resistance value at extremely low temperature becomes high accordingly, so it can be considered that the residual resistance ratio is slightly lower than that of Comparative Example 5. For Examples 2 and 3, although the residual resistance ratio was not measured, it can be considered that the average crystal grain size of the fine grain region is larger and the number of grain boundaries is smaller than that of Example 1, so it can be predicted that the residual resistance ratio is higher than that of Example 1.

[0102] This application claims priority based on Japanese Patent Application No. 2020-129167, filed on July 30, 2020. Japanese Patent Application No. 2020-129167 is incorporated herein by reference.

[0103] Industrial Applicability

[0104] The aluminum member according to the embodiment of the present invention has a purity of 5N or more and has sufficient strength in at least a portion thereof, and is therefore suitable as, for example, an electrical and thermal conductive material for use at extremely low temperatures.

[0105] Description of Reference Numerals

[0106] 1 Fine grain region

[0107] 2 Intermediate grain region

[0108] 3 Coarse grain area.

Claims

1. An aluminum component comprising a fine grain region having a grain size of less than 20 μm, an intermediate grain region having a grain size of 20 μm or more and less than 150 μm, and a coarse grain region having a grain size of 150 μm or more, and The aluminum member has a purity of 99.999 mass % or more.

2. The aluminum member according to claim 1, wherein The average crystal grain size of the fine crystal grain region is 5 μm or less.

3. The aluminum member according to claim 1 or 2, wherein: On at least one surface, the fine grain region exists continuously for 0.01 mm 2 The area above. 4 . An electrical and thermal conductive material for use at extremely low temperatures, comprising the aluminum member according to claim 1 .

5. A method for manufacturing an aluminum component according to any one of claims 1 to 3, comprising a friction stirring step of pressing and moving a rotating cylindrical fixture on the surface of an aluminum plate having a purity of 99.999% by mass or more, wherein the moving speed of the cylindrical fixture is 100 mm / min or less.

6. The method according to claim 5, wherein: In the friction stirring step, the cylindrical jig is moved with its rotation axis inclined by more than 3° from a perpendicular line to the surface of the aluminum plate in a direction opposite to the moving direction of the cylindrical jig.